Wawasan Mahasiswa Universitas Mitra Karya dalam Berwirausaha - Suroyo Suroyo (Peneliti.net, 2022)
Entrepreneurship education being one of the important fields in the world of Education, it is time to carefully consider individual learning experiences that are incorporated into the formal curriculum for teaching entrepreneurship. In this article, we use a case study approach to consider events hosted by Universitas Mitra Karya students as a university in a regional context and note the call for more entrepreneurs to develop socio-economic activities. Observations and interviews with student leaders and two other students and their architecture benefited from the university's preferred top-down approach to motivating students to become entrepreneurs, but was faced with grassroots backlash. Clarify existing problems. Faced with participation in entrepreneurial activities